Energy conversion performance of porous ZrTe hybrid derived from chemical transformation of Zr(OH)4. (15th November 2022) - Manzoor, Sumaira; Abid, Abdul Ghafoor; Mehar-Un-Nisa,; Hussain, Fayyaz; Shah, Afzal; Pashameah, Rami Adel; Alzahrani, Eman; El-Bahy, Salah M.; Taha, T.A.; Ashiq, Muhammad Naeem
Graphical abstract: Highlights: Hydrothermal treatment was employed for the synthesis of ZrTe. ZrTe deposited on carbon cloth (CC) perform well for OER. ZrTe/CC exhibits lower overpotential of 294 mV and smaller Tafel slope of 71 mV dec -1 . The high performance of ZrTe/CC was also confirmed via the density functional theory (DFT). Abstract: Next-generation fuels are produced via electrochemical water splitting technology, and energy conversion processes can be improved by fabricating high-performance oxygen evolution (OER) electrocatalysts. Among all types of electrocatalysts, alternative, cheap, and high-performance OER catalysts are the metal tellurides. Here in the present report, the novel ZrTe has directly grown on carbon cloth (CC) and outperforms OER due to its 3D shell-like structure, high conductivity, and porous nature. Hydrothermal conditions are employed to promote an anion-exchange process that leads to zirconium tellurium nanostructure from synthesized tellurium ions and hydroxide of the zirconium hexagonal nanosheets. The electrochemical measurements are performed using modified electrodes, and are tested in the alkaline environment using cyclic voltammetry (CV), linear sweep voltammetry (LSV), and a constant potential chronoamperometry (CA). The ZrTe/CC resulted in a lower overpotential of 294 mV with a smaller Tafel slope of 71 mV dec −1 and high stability of 45 h towards OER because of its unique shape resulting in large electrochemical active zones and more active sites without any binding agent. Additionally, the present study also validates that ZrTe/CC hybrid is more active towards OER via the density functional theory (DFT) and theoretical calculations, as our findings show that it is possible to produce multi-metal telluride-based materials that can be exceptionally efficient and stable electrocatalyst for OER, and also in future applications.